2013
DOI: 10.1161/hypertensionaha.112.199356
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Programming of Hypertension Induces Sympathetic Overactivity in Response to Physical Stress

Abstract: Small for gestational age infants are known to develop hypertension in adulthood. This prenatal programming of hypertension (PPH) can result from several insults including maternal dietary protein deprivation, uteroplacental insufficiency and prenatal administration of glucocorticoids. The mechanisms underlying the development of hypertension remain unclear although the sympathetic nervous system has been indirectly implicated. This study was designed to directly measure renal sympathetic activity (RSNA) both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 49 publications
6
62
0
Order By: Relevance
“…In the only other study in which gross renal sympathetic nerve activity was recorded in male offspring of dams fed a low protein diet, baseline renal sympathetic nerve activity was comparable to that of controls, but showed larger increases during static muscle contraction. 26 In the few reports of single unit MSNA in humans, mean frequency of single unit MSNA was low in normotensives (≈0.3 Hz), higher in established essential hypertensives (≈0.6 Hz), and higher still in borderline hypertensives (≈0.75 Hz), consistent with sympathetic hyperactivity preceding the full development of essential hypertension. 27 Further, in normotensives, couplets or higher multiples of impulses were uncommon, instantaneous frequencies being <1 Hz in ≈50% of units, 28 but far more common in essential hypertension.…”
Section: Prenatal Hypoxia and Msnamentioning
confidence: 90%
“…In the only other study in which gross renal sympathetic nerve activity was recorded in male offspring of dams fed a low protein diet, baseline renal sympathetic nerve activity was comparable to that of controls, but showed larger increases during static muscle contraction. 26 In the few reports of single unit MSNA in humans, mean frequency of single unit MSNA was low in normotensives (≈0.3 Hz), higher in established essential hypertensives (≈0.6 Hz), and higher still in borderline hypertensives (≈0.75 Hz), consistent with sympathetic hyperactivity preceding the full development of essential hypertension. 27 Further, in normotensives, couplets or higher multiples of impulses were uncommon, instantaneous frequencies being <1 Hz in ≈50% of units, 28 but far more common in essential hypertension.…”
Section: Prenatal Hypoxia and Msnamentioning
confidence: 90%
“…This characteristic EPR overactivity has been shown to manifest not only in SHR but also in other models of the disease such as prenatally programmed hypertension (41,44) and angiotensin II-induced hypertension (24). In SHR, 3 mo of voluntary wheel running attenuated the cardiovascular and sympathetic responses to EPR activation.…”
Section: Exercise Training Attenuates Epr Function In Shrmentioning
confidence: 99%
“…Recently, in the rat model of prenatal programming of hypertension (PPH), EPR dysfunction was found which may play a role in developing hypertension. Mizuno and colleagues 90) demonstrated that the RSNA and pressor responses to contraction were exaggerated in the PPH rats. Moreover, orally-administered treatment with angiotensin converting enzyme inhibitor enalapril in the PPH rats could reduce the exaggerated EPR responses 91) .…”
Section: Contribution Of Rat Studies To Understanding Of Mechanisms Umentioning
confidence: 99%